SURVIVAL RATE AND GROWTH OF JUVENILE SANDFISH (Holothuria scabra) IN VARIOUS REARING CONDITIONS - Indriana, Lisa Fajar; Firdaus, Muhammad; Supono, .; Munandar, Hendra (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2017)
Techniques for producing Holothuria scabra or sandfish sea cucumbers from aquaculture have been developed rapidly in the recent years to address the issues of decreasing sandfish population and increasing market demand. During the process of culturing H. scabra, the early stages of sandfish (i.e. larvae and juveniles) are the most critical of the development. Therefore, the Research and Development Division of the Marine Bio Industry â LIPI conducted a study to assess the growth performance of juvenile H. scabraÂ ultured in four different rearing conditions: (i) indoor concrete tank, (ii) indoor fiberglass tank, (iii) outdoor concrete tank with 1 mm hapa mesh, and (iv) outdoor concrete tank with 3 mm hapa mesh. Each of the rearing condition was set with an initial juvenile density of 15 juveniles per tank with a mean initial weight of 14 g, and fed ad libitum with a mixed feed consisting of Enhalus acoroides sea grass, Pennisetum purpureum napier and cow manure. The experiments were conducted for 20 weeks between April 26 - September 23, 2013. After the experimental period, juveniles reared in the outdoor concrete tank with 1 mm mesh show the best performance with respect to their survival rate (48.89 Â± 3.85 %),mean final weight (22.07 Â± 1.01 g), final biomass (162.05 Â± 18.17 g) and specific growth rate (0.15 Â± 0.03% per day). Further studies that combine rearing conditions with different bottom substrates as well as investigating the effect of light are needed to optimize the production of H. scabra from aquaculture.